Measuring income inequality in Malaysia based on household income survey - Muhammad Aslam Mohd Safari; Nurulkamal Masseran; Kamarulzaman Ibrahim; Saiful Izzuan Hussain (Penerbit Universiti Kebangsaan Malaysia, 2019)
Several policies have been introduced by Malaysian government with the aim of reducing the income inequality among the citizens. This study examines the changes in income inequality based on three different indices, which are Gini, Atkinson and generalized entropy using the household incomes data available from the surveys conducted in 2007, 2009, 2012 and 2014. Modification for each index is employed by taking sample weights into account for better measurement. Lorenz curves are fitted to the data to describe how the incomes of different household income groups are distributed over the time period. All the indices show a decreasing trend from 2007 to 2014, indicating an overall improvement of income distribution. The proportions of income earned by the low income groups have increased from 14.25% in 2007 to 16.28% in 2014 after taking economic pie from the higher income group while the middle class remains unchanged.